2013
DOI: 10.1007/s00520-013-1810-y
|View full text |Cite
|
Sign up to set email alerts
|

Emerging evidence on the pathobiology of mucositis

Abstract: The ultimate goal of mucositis researchers is to identify the most appropriate targets for therapeutic interventions and to be able to predict toxicity risk and personalize interventions to genetically suitable patients. Continuing research efforts are needed to further our understanding of mucositis pathobiology and the pharmacogenomics of toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 97 publications
1
108
0
5
Order By: Relevance
“…This contrasts with oral mucositis caused by conventional high‐dose chemotherapy and for which the pathobiology has been studied for the past two decades (Fig. 2) 2, 6, 23, 24, 25, 26, 27. Insights into the mechanism of action of mTOR inhibitors and naturally occurring oral mucosal lesions such as recurrent aphthous ulceration may thus be valuable in informing future research directions involving mIAS.…”
Section: Phenotype Incidence and Pathobiology Of Mtor Inhibitor–assmentioning
confidence: 99%
“…This contrasts with oral mucositis caused by conventional high‐dose chemotherapy and for which the pathobiology has been studied for the past two decades (Fig. 2) 2, 6, 23, 24, 25, 26, 27. Insights into the mechanism of action of mTOR inhibitors and naturally occurring oral mucosal lesions such as recurrent aphthous ulceration may thus be valuable in informing future research directions involving mIAS.…”
Section: Phenotype Incidence and Pathobiology Of Mtor Inhibitor–assmentioning
confidence: 99%
“…Epithelial tissue and ECM play a significant role in maintaining the integrity and function of the epithelial layer [2,9]. Intercellular occluding junctions act as a selectively permeable barrier to fluid flow between cells.…”
Section: Tissue Integritymentioning
confidence: 99%
“…Intercellular occluding junctions act as a selectively permeable barrier to fluid flow between cells. A variety of physiological and pharmacological stimuli can modulate the barrier properties 9 . A number of studies have demonstrated drastic changes in tight junction permeability resulting from the action of certain cytokines, such as tumor necrosis factor (TNF-α), IL-1 and IL-6 7,[10][11][12] .…”
Section: Tissue Integritymentioning
confidence: 99%
“…For most other combinations as well as most monotherapies, rates of 10-20% are common [25]. Lack of oral care, xerostomia, genetic factors, renal/hepatic insufficiency, and previous antitumor therapy of the head and neck area are known to increase the risk of mucositis [23]. Symptoms may range from painless erythema to ulceration, bleeding, and pain.…”
Section: Mucositismentioning
confidence: 99%
“…The pathogenesis is believed to be a complex mechanism of damage to DNA, upregulation of proinflammatory cytokines and enzymes, apoptosis, ulceration, as well as secondary infection [23]. With novel therapies, oral toxicities may present in various different ways [24], including, but not limited to, dysgeusia, aphthoid lesions, mucosal bleeding, xerostomia, glossitis, lichenoid reactions, as well as hyperkeratosis and gingival hyperplasia.…”
Section: Mucositismentioning
confidence: 99%